Brain activation in individuals suffering from bulimia nervosa and control subjects during sweet and sour taste stimuli - Armon, Daphna Bardin; Bick, Atira; Florentin, Sharon; Laufer, Sofia; Barkai, Gabriel; Bachar, Eytan; Hendler, Talma; Bonne, Omer; Keller, Shikma (Frontiers in Psychiatry, 2023)
Introduction: Episodes of eating great quantities of extremely sweet and often aversive tasting food are a hallmark of bulimia nervosa. This unique eating pattern led researchers to seek and find differences in taste perception between patients and healthy control subjects. However, it is currently not known if these originate from central or peripheral impairment in the taste perception system. In this cross-sectional study, we compare brain response to sweet and sour stimuli in 5 bulimic and 8 healthy women using functional Magnetic Resonance Imaging (fMRI). Materials and methods: Sweet, sour, and neutral, (colorless and odorless) taste solutions were administered and presented to subjects while undergoing fMRI scanning. Data were analyzed using a block design paradigm. Results: Between-group differences in brain activation in response to both sweet and sour tastes were found in 11 brain regions, including the operculum, anterior cingulate cortex, midbrain, and cerebellum. These are all considered central to the perception and processing of taste. Conclusions: Our data suggest propose that sweet and sour tastes may have reward or aversion eliciting attributes in patients suffering from bulimia nervosa not found in healthy subjects, suggesting that alteration in taste processing may be a core dysfunction in Bulimia Nervosa.